Improvement Competency of Teachers and Students to Improve Capabilities in Security Awareness Aspects at SMK Pustek Serpong: Peningkatan Kompetensi Guru dan Siswa untuk Meningkatkan Kemampuan pada Aspek Security Awareness di SMK Pustek Serpong - Damanik, Hillman Akhyar; Anggraeni, Merry; Nusantari, Farida Ayu Avisena (Universitas Lancang Kuning, 2023)
Program Kemitraan Kepada Masyarakat (PKM), we propose in PUSTEK Serpong Vocational School that is targeted is Computer and Network Engineering (TKJ) students. Until now there have been several obstacles that occurred during the implementation and learning activities, namely in the previous curriculum there were materials and teaching materials for Network Security and since 2013 the curriculum and teaching materials have disappeared, and there is a need for discussion and material. In the form of learning modules for Network Security competencies. The results of this PKM are expected to gain an increase in scientific capacity and competence by 80% for Network Security training at the PUSTEK Serpong Vocational School. So that at the end of this PKM activity, the proposer hopes and tries with the knowledge and application of the training provided to students, to be able to motivate and provide Information Communication Technology (ICT) knowledge, especially in the field of Computer Network technology and Network Security, so that future students can be prepared use in the world and work industry.